ENHANCING DEVELOPER PRODUCTIVITY WITH AI-DRIVEN TOOLS: THE FUTURE OF CODING ASSISTANCE - Kartheek Medhavi Penagamuri Shriram (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
This article explores the transformative impact of AI-driven tools on software development practices, examining how these technologies are reshaping developer productivity, code quality, and overall software engineering processes. The article analyzes various aspects of AI integration in development environments, including package management systems, code embeddings, and retrieval-augmented generation, while also investigating the ethical considerations and evolving role of developers. Through a comprehensive analysis of multiple research studies and industry implementations, this article demonstrates how AI-assisted development is revolutionizing traditional workflows, enhancing code quality, reducing technical debt, and accelerating innovation cycles across different sectors. The article also addresses the significance of proper AI tool optimization, the importance of developer skill evolution, and the broader societal implications of these technological advancements in software development.